2009
DOI: 10.1097/brs.0b013e318198c5f2
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Spine Fusion in Obese and Morbidly Obese Patients

Abstract: Obese and morbidly obese patients have multiple comorbidities, and the spinal surgeon should be prepared to encounter perioperative complexities. Operative times are longer in comparison with normal weight patients with a higher incidence of postoperative complications. No weight loss occurs after spinal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
107
1
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 145 publications
(121 citation statements)
references
References 11 publications
6
107
1
4
Order By: Relevance
“…Similarly, Vaidya et al reported on surgical parameters and clinical outcomes after open lumbar fusion in obese patients. They found that although surgical blood loss and peri-operative complications were significantly higher in obese patients, post-operative ODI was not affected by obesity [12]. Contradictory findings were published by Gepstein et al, where obesity was found to be a significant independent risk factor for worse preand post-operative VAS scores as well as Barthel indices (assessment of ability to perform ADLs) in patients undergoing open lumbar spine surgery.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Similarly, Vaidya et al reported on surgical parameters and clinical outcomes after open lumbar fusion in obese patients. They found that although surgical blood loss and peri-operative complications were significantly higher in obese patients, post-operative ODI was not affected by obesity [12]. Contradictory findings were published by Gepstein et al, where obesity was found to be a significant independent risk factor for worse preand post-operative VAS scores as well as Barthel indices (assessment of ability to perform ADLs) in patients undergoing open lumbar spine surgery.…”
Section: Discussionsupporting
confidence: 53%
“…Additionally, obese patients that were managed operatively demonstrated significantly less improvement and lower final follow up values in the Sciatica Bothersomeness and Low Back Pain Bothersomeness Indices [42]. Though seemingly at odds with other clinical studies [12,20,[34][35][36], this as-treated analysis of the SPORT study has the benefit of a prospective design with large samples from multiple geographic locals and medical centers and long-term follow up which affords favorable generalizability of its results to true values expected in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity is a growing public health problem with evidence of a shift in population trends towards higher BMI. The number of patients with elevated BMI undergoing spine procedures, therefore, is rising [67]. Patients with higher BMI have been found to have lower serum and tissue concentrations of prophylactic antibiotics and, thus, inadequate protection against SSI [68].…”
Section: Odds Ratiomentioning
confidence: 99%
“…Given the previous literature reporting satisfactory outcomes with lumbar fusion in obese patients, 5,14,15,22,25,29 we hypothesized that obese and nonobese patients would have comparable clinical benefit following lumbar spine surgery regardless of whether lumbar fusion was part of the procedure. Therefore, the purpose of the current study was to compare the outcomes of obese versus nonobese patients who had undergone surgical treatment for the diagnosis of lumbar spinal stenosis (LSS).…”
mentioning
confidence: 99%